Environmental and economic perspectives of concrete with high mineral addition content: a case study - Isaia, Geraldo Cechella (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2008)
Concrete, the most consumed building material in the world, requires a large amount of natural resources, and its production has a strong impact on the increase of the greenhouse effect. Fly ash and ground granulated blast-furnace slag are highly available industrial by-products, which can replace cement in high contents with significant advantages. This paper presents a case study in which the replacement of cement in 90% by those two mineral additions has reduced costs in 5% in costs, energy consumption in 58%, and CO2 emission in 81%, and increased the durability mean index in 34%. The use of 90% mineral additions in 5.4% (351 Mm³) of the world’s concrete production, from 2005, could save 78Mt of cement, resulting in the maintenance of world cement production at the level of 1.78 Mt/year, without future increases. There would be an annual reduction of 130 Mt on the extraction of raw materials, an economy of 0.4 EJ in energy - the same consumed by Denmark - and a 8.7% reduction of production costs of concrete with 90% of fly ash and blast-furnace slag, compared to conventional Portland cement concrete.